Making movies - Lumet, Sidney (Vintage, 1995)
Why does a director choose a particular script? What must they do in order to keep actors fresh and truthful through take after take of a single scene? How do you stage a shootout--involving more than one hundred extras and three colliding taxis--in the heart of New York's diamond district? What does it take to keep the studio honchos happy? From the first rehearsal to the final screening, Making Movies is a master's take, delivered with clarity, candor, and a wealth of anecdote. For in this book, Sidney Lumet, one of our most consistently acclaimed directors, gives us both a professional memoir and a definitive guide to the art, craft, and business of the motion picture. Drawing on forty years of experience on movies that range from Long Day's Journey into Night to Network and The Verdict--and with such stars as Katharine Hepburn, Paul Newman, Marlon Brando, and Al Pacino--Lumet explains how painstaking labor and inspired split-second decisions can result in two hours of screen magic.